Cover Feature: Thermodynamic Considerations on the Oxidation State of Co/γ‐Al2O3 and Ni/γ‐Al2O3 Catalysts under Dry and Steam Reforming Conditions (ChemCatChem 4/2018). Issue 4 (21st February 2018) - Giehr, Andreas; Maier, Lubow; Schunk, Stephan A.; Deutschmann, Olaf
Abstract : The Cover Feature illustrates the catalytic cycle of cobalt oxidation, methane cracking, and carbon oxidation, which finally regenerates the catalyst surface. In their Full Paper, A. Giehr et al. have combined thermodynamic calculations and steady state reactor simulations under methane dry reforming conditions to investigate the difference in behavior of Ni‐ and Co‐based materials. Whereas Ni is preferably reduced over the whole length of the reactor, Co can be present in an oxidized state depending on the degree of conversion and thus on the axial position within the reactor. Beside the Langmuir‐Hinshelwood mechanism, which occurs on metallic surfaces, the presence of partially oxidized cobalt opens up the possibility for an additional, Mars‐van Krevelen‐type reaction pathway, which may explain the higher coking resistance of Co‐ over Ni‐based catalysts.